2012
DOI: 10.1364/ol.37.001127
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical application of z-dependent gain coefficient to describe amplified spontaneous emission

Abstract: Based on the geometrical modeling of the unified gain coefficient and the reported amplified spontaneous emission (ASE) output energy measurement ε(ASE) versus amplifying excitation length, l(AMP) in a KrF laser oscillator, we managed, as an example, to explain the ASE output energy behavior both numerically and analytically. In this approach, introducing the ASE gain-coefficient profile for the KrF laser, g(0,KrF)(ASE), was not avoidable. It was found that while the g(0,KrF)(ASE) profile follows the introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…In our previous report we showed that by using the photon density rate equation it is possible to predict the ASE output energy ε ASE versus medium excitation length, l AMP , for KrF lasers [14,15]. Consequently, we managed to explain the reported experimental measurements that appeared in [16].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In our previous report we showed that by using the photon density rate equation it is possible to predict the ASE output energy ε ASE versus medium excitation length, l AMP , for KrF lasers [14,15]. Consequently, we managed to explain the reported experimental measurements that appeared in [16].…”
Section: Introductionmentioning
confidence: 94%
“…, where g ν 0 0 is given by equation ( 2), and x = 2(ν − ν 0 )/ ν 0 is the normalized frequency offset [21,22]. For µ = 0 and ν = ν 0 the ASE intensity was calculated numerically, as in [14,15], where we obtained accordingly that m 1 = 0.001 cm −1 and γ max L = 4.5. In the present work for µ = 1, and by considering again that ν = ν 0 , we performed the numerical calculation and the results are given in figure 1, where in contrast to the case for [14,15], the ASE output energy, ε ASE , is given on a logarithmic scale for a better visualization of the fitting of the experimental data to the proposed model of the geometrically dependent gain coefficient (GDGC).…”
Section: The Theoretical Approachmentioning
confidence: 99%
“…The analytical approach to explain the ASE behavior, using a four level system for a homogeneously broadened transition, has led to an analytical expression for the ASE output energy or intensity, and has been introduced in Refs. [22] and [23]. Thus, the details of this part of the calculation are not given here, except some relevant parts for better understanding of the proposed method.…”
Section: Theoretical Approachmentioning
confidence: 99%
“…( 4) is γ(z)g ν 0 (z)hν/σ ν stim τ sp , and the solution of Eq. ( 4) for I ν (z) is given by the following expression: [22,23]…”
Section: Homogeneously Broadened Transitionmentioning
confidence: 99%
See 1 more Smart Citation